test: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
(32 intermediate revisions by the same user not shown)
Line 1: Line 1:
{| class="wikitable sortable"
{{DISPLAYTITLE:Ey let me change the title god damn it}}
 
<div style="-moz-column-count:2; column-count:2;">
; Notation : [[1.1|1.1 Special Notation]]<br>
; Areas : [[1.2|1.2 Elementary Algebra]]<br>[[1.3|1.3 Determinants]]<br>[[1.4|1.4 Calculus of One Variable]]<br>[[1.5|1.5 Calculus of Two or More Variables]]<br>[[1.6|1.6 Vectors and Vector-Valued Functions]]<br>[[1.7|1.7 Inequalities]]<br>[[1.8|1.8 Fourier Series]]<br>[[1.9|1.9 Calculus of a Complex Variable]]<br>[[1.10|1.10 Functions of a Complex Variable]]<br>[[1.11|1.11 Zeros of Polynomials]]<br>[[1.12|1.12 Continued Fractions]]<br>[[1.13|1.13 Differential Equations]]<br>[[1.14|1.14 Integral Transforms]]<br>[[1.15|1.15 Summability Methods]]<br>[[1.16|1.16 Distributions]]<br>[[1.17|1.17 Integral and Series Representations of the Dirac Delta]]<br>
<br>
 
</div>
 
 
<div style="width: 100%; height: 75vh; overflow: auto;">
{| class="wikitable sortable" style="margin: 0;"
|-
|-
! DLMF !! Formula !! Constraints !! Maple !! Mathematica !! Symbolic<br>Maple !! Symbolic<br>Mathematica !! Numeric<br>Maple !! Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | DLMF  
! scope="col" style="position: sticky; top: 0;" | Formula  
! scope="col" style="position: sticky; top: 0;" | Constraints  
! scope="col" style="position: sticky; top: 0;" | Maple
! scope="col" style="position: sticky; top: 0;" | Mathematica
! scope="col" style="position: sticky; top: 0;" | Symbolic<br>Maple
! scope="col" style="position: sticky; top: 0;" | Symbolic<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Maple
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-
| [https://dlmf.nist.gov/4.4.E1 4.4.E1] || [[Item:Q1535|<math>\ln@@{1} = 0</math>]] - Mit Item:QID<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\ln@@{1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>ln(1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Log[1] == 0</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|-
|-
| [https://dlmf.nist.gov/1.2.E1 1.2.E1] || [[Item:Q30|<math>\binom{n}{k} = \frac{n!}{(n-k)!k!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 80%;" inline>\binom{n}{k} = \frac{n!}{(n-k)!k!}</syntaxhighlight> || <math></math> || <syntaxhighlight>binomial(n,k) = (factorial(n))/(factorial(n - k)*factorial(k))</syntaxhighlight> || <syntaxhighlight>Binomial[n,k] == Divide[(n)!,(n - k)!*(k)!]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 9]
| [https://dlmf.nist.gov/4.4.E1 4.4.E1] || <math qid="Q1535">\ln@@{1} = 0</math> - Mit Math-QID<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\ln@@{1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>ln(1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Log[1] == 0</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|-
|-
| [https://dlmf.nist.gov/1.5.E4 1.5.E4] || [[Item:Q121|<math>\pderiv{f}{y} = D_{y}f</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\pderiv{f}{y} = D_{y}f</syntaxhighlight> || <math></math> || <syntaxhighlight>diff(f, y) = D[y]*f</syntaxhighlight> || <syntaxhighlight>D[f, y] == Subscript[D, y]*f</syntaxhighlight> || Failure || Failure || <div class="toccolours mw-collapsible mw-collapsed">Failed [300 / 300]<div class="mw-collapsible-content"><syntaxhighlight>Result: -.5000000004-.8660254040*I
| [https://dlmf.nist.gov/1.2.E1 1.2.E1] || [[Item:Q30|<math>\binom{n}{k} = \frac{n!}{(n-k)!k!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 80%;" inline>\binom{n}{k} = \frac{n!}{(n-k)!k!}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(n,k) = (factorial(n))/(factorial(n - k)*factorial(k))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[n,k] == Divide[(n)!,(n - k)!*(k)!]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 9]
Test Values: {f = 1/2*3^(1/2)+1/2*I, y = -1.5, D[y] = 1/2*3^(1/2)+1/2*I}</syntaxhighlight><br><syntaxhighlight>Result: .8660254040-.5000000004*I
Test Values: {f = 1/2*3^(1/2)+1/2*I, y = -1.5, D[y] = -1/2+1/2*I*3^(1/2)}</syntaxhighlight><br><syntaxhighlight>Result: -.8660254040+.5000000004*I
Test Values: {f = 1/2*3^(1/2)+1/2*I, y = -1.5, D[y] = 1/2-1/2*I*3^(1/2)}</syntaxhighlight><br><syntaxhighlight>Result: .5000000004+.8660254040*I
Test Values: {f = 1/2*3^(1/2)+1/2*I, y = -1.5, D[y] = -1/2*3^(1/2)-1/2*I}</syntaxhighlight><br>... skip entries to safe data</div></div> || <div class="toccolours mw-collapsible mw-collapsed">Failed [300 / 300]<div class="mw-collapsible-content"><syntaxhighlight>Result: Complex[-0.5000000000000001, -0.8660254037844386]
Test Values: {Rule[f, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[y, -1.5], Rule[Subscript[D, y], Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}</syntaxhighlight><br><syntaxhighlight>Result: Complex[0.8660254037844387, -0.49999999999999994]
Test Values: {Rule[f, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[y, -1.5], Rule[Subscript[D, y], Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}</syntaxhighlight><br>... skip entries to safe data</div></div>
|-
|-
| [https://dlmf.nist.gov/18.35.E4 18.35.E4] || [[Item:Q6043|<math>\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n}}{n!}e^{\iunit n\theta}\*\genhyperF{2}{1}@@{-n,\lambda+\iunit\tau_{a,b}(\theta)}{-n-\lambda+1+\iunit\tau_{a,b}(\theta)}{e^{-2\iunit\theta}} = \sum_{\ell=0}^{n}\frac{\Pochhammersym{\lambda+\iunit\tau_{a,b}(\theta)}{\ell}}{\ell!}\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n-\ell}}{(n-\ell)!}e^{\iunit(n-2\ell)\theta}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; white-space:break-spaces" inline>\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n}}{n!}e^{\iunit n\theta}\*\genhyperF{2}{1}@@{-n,\lambda+\iunit\tau_{a,b}(\theta)}{-n-\lambda+1+\iunit\tau_{a,b}(\theta)}{e^{-2\iunit\theta}} = \sum_{\ell=0}^{n}\frac{\Pochhammersym{\lambda+\iunit\tau_{a,b}(\theta)}{\ell}}{\ell!}\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n-\ell}}{(n-\ell)!}e^{\iunit(n-2\ell)\theta}</syntaxhighlight> || <math>0 < \theta, \theta < \pi</math> || <syntaxhighlight lang=mathematica>(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n))/(factorial(n))*exp(I*n*theta)* hypergeom([- n , lambda + I*((a*cos(theta)+ b)/(sin(theta)))], [- n - lambda + 1 + I*((a*cos(theta)+ b)/(sin(theta)))], exp(- 2*I*theta)) = sum((pochhammer(lambda + I*((a*cos(theta)+ b)/(sin(theta))), ell))/(factorial(ell))*(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n - ell))/(factorial(n - ell))*exp(I*(n - 2*ell)*theta), ell = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n],(n)!]*Exp[I*n*\[Theta]]* HypergeometricPFQ[{- n , \[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, {- n - \[Lambda]+ 1 + I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, Exp[- 2*I*\[Theta]]] == Sum[Divide[Pochhammer[\[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), \[ScriptL]],(\[ScriptL])!]*Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n - \[ScriptL]],(n - \[ScriptL])!]*Exp[I*(n - 2*\[ScriptL])*\[Theta]], {\[ScriptL], 0, n}, GenerateConditions->None]</syntaxhighlight> || Error || Successful || - || Successful [Tested: 300]
|-
| [https://dlmf.nist.gov/1.2.E1 1.2.E1] || [[Item:Q30|<math>\frac{n!}{(n-k)!k!} = \binom{n}{n-k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{n!}{(n-k)!k!} = \binom{n}{n-k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(factorial(n))/(factorial(n - k)*factorial(k)) = binomial(n,n - k)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[(n)!,(n - k)!*(k)!] == Binomial[n,n - k]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 9]
|-
| [https://dlmf.nist.gov/1.2.E6 1.2.E6] || [[Item:Q35|<math>\frac{(-1)^{k}\Pochhammersym{-z}{k}}{k!} = (-1)^{k}\binom{k-z-1}{k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{(-1)^{k}\Pochhammersym{-z}{k}}{k!} = (-1)^{k}\binom{k-z-1}{k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>((- 1)^(k)* pochhammer(- z, k))/(factorial(k)) = (- 1)^(k)*binomial(k - z - 1,k)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[(- 1)^(k)* Pochhammer[- z, k],(k)!] == (- 1)^(k)*Binomial[k - z - 1,k]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 21]
|-
| [https://dlmf.nist.gov/1.2.E7 1.2.E7] || [[Item:Q36|<math>\binom{z+1}{k} = \binom{z}{k}+\binom{z}{k-1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{z+1}{k} = \binom{z}{k}+\binom{z}{k-1}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(z + 1,k) = binomial(z,k)+binomial(z,k - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[z + 1,k] == Binomial[z,k]+Binomial[z,k - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 21]
|-
| [https://dlmf.nist.gov/1.2.E8 1.2.E8] || [[Item:Q37|<math>\sum^{m}_{k=0}\binom{z+k}{k} = \binom{z+m+1}{m}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum^{m}_{k=0}\binom{z+k}{k} = \binom{z+m+1}{m}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(binomial(z + k,k), k = 0..m) = binomial(z + m + 1,m)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Binomial[z + k,k], {k, 0, m}, GenerateConditions->None] == Binomial[z + m + 1,m]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 21]
|- style="background: #ffeaa7;"
| [https://dlmf.nist.gov/1.2.E10 1.2.E10] || [[Item:Q39|<math>na+\tfrac{1}{2}n(n-1)d = \tfrac{1}{2}n(a+\ell)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>na+\tfrac{1}{2}n(n-1)d = \tfrac{1}{2}n(a+\ell)</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>n*a +(1)/(2)*n*(n - 1)*d = (1)/(2)*n*(a + ell)</syntaxhighlight> || <syntaxhighlight lang=mathematica>n*a +Divide[1,2]*n*(n - 1)*d == Divide[1,2]*n*(a + \[ScriptL])</syntaxhighlight> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-
| [https://dlmf.nist.gov/1.2.E22 1.2.E22] || [[Item:Q51|<math>M(r) = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>M(r) = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r)) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>((Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r)) == 0</syntaxhighlight> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-
| [https://dlmf.nist.gov/1.2#Ex1 1.2#Ex1] || [[Item:Q54|<math>M(1) = A</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>M(1) = A</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>M(1) = ((a[1]+ a[2]+ .. + a[n])/(n))</syntaxhighlight> || <syntaxhighlight lang=mathematica>M[1] == (Divide[Subscript[a, 1]+ Subscript[a, 2]+ \[Ellipsis]+ Subscript[a, n],n])</syntaxhighlight> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-
| [https://dlmf.nist.gov/1.2#Ex2 1.2#Ex2] || [[Item:Q55|<math>M(-1) = H</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>M(-1) = H</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>M(- 1) = H</syntaxhighlight> || <syntaxhighlight lang=mathematica>M[- 1] == H</syntaxhighlight> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-
| [https://dlmf.nist.gov/1.2.E26 1.2.E26] || [[Item:Q56|<math>\lim_{r\to 0}M(r) = G</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\lim_{r\to 0}M(r) = G</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>limit((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r), r = 0) = ((a[1]*a[2] .. a[n])^(1/n))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Limit[(Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r), r -> 0, GenerateConditions->None] == ((Subscript[a, 1]*Subscript[a, 2] \[Ellipsis]Subscript[a, n])^(1/n))</syntaxhighlight> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>

Latest revision as of 06:40, 28 June 2021


Notation
1.1 Special Notation
Areas
1.2 Elementary Algebra
1.3 Determinants
1.4 Calculus of One Variable
1.5 Calculus of Two or More Variables
1.6 Vectors and Vector-Valued Functions
1.7 Inequalities
1.8 Fourier Series
1.9 Calculus of a Complex Variable
1.10 Functions of a Complex Variable
1.11 Zeros of Polynomials
1.12 Continued Fractions
1.13 Differential Equations
1.14 Integral Transforms
1.15 Summability Methods
1.16 Distributions
1.17 Integral and Series Representations of the Dirac Delta



DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
4.4.E1 ln 1 = 0 1 0 {\displaystyle{\displaystyle\ln 1=0}} - Mit Item:QID
\ln@@{1} = 0

ln(1) = 0
Log[1] == 0
Successful Successful - Successful [Tested: 1]
4.4.E1 ln 1 = 0 1 0 {\displaystyle{\displaystyle\ln 1=0}} - Mit Math-QID
\ln@@{1} = 0

ln(1) = 0
Log[1] == 0
Successful Successful - Successful [Tested: 1]
1.2.E1 ( n k ) = n ! ( n - k ) ! k ! binomial 𝑛 𝑘 𝑛 𝑛 𝑘 𝑘 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{n}{k}=\frac{n!}{(n-k)!k!}}}
\binom{n}{k} = \frac{n!}{(n-k)!k!}

binomial(n,k) = (factorial(n))/(factorial(n - k)*factorial(k))
Binomial[n,k] == Divide[(n)!,(n - k)!*(k)!]
Successful Successful - Successful [Tested: 9]
18.35.E4 ( λ - i τ a , b ( θ ) ) n n ! e i n θ F 1 2 ( - n , λ + i τ a , b ( θ ) - n - λ + 1 + i τ a , b ( θ ) ; e - 2 i θ ) = = 0 n ( λ + i τ a , b ( θ ) ) ! ( λ - i τ a , b ( θ ) ) n - ( n - ) ! e i ( n - 2 ) θ Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 𝜃 Gauss-hypergeometric-F-as-2F1 𝑛 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝜆 1 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 superscript 𝑒 2 imaginary-unit 𝜃 superscript subscript 0 𝑛 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 2 𝜃 {\displaystyle{\displaystyle\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(\theta)% \right)_{n}}}{n!}e^{\mathrm{i}n\theta}\*{{}_{2}F_{1}}\left({-n,\lambda+\mathrm% {i}\tau_{a,b}(\theta)\atop-n-\lambda+1+\mathrm{i}\tau_{a,b}(\theta)};e^{-2% \mathrm{i}\theta}\right)=\sum_{\ell=0}^{n}\frac{{\left(\lambda+\mathrm{i}\tau_% {a,b}(\theta)\right)_{\ell}}}{\ell!}\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(% \theta)\right)_{n-\ell}}}{(n-\ell)!}e^{\mathrm{i}(n-2\ell)\theta}}}
\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n}}{n!}e^{\iunit n\theta}\*\genhyperF{2}{1}@@{-n,\lambda+\iunit\tau_{a,b}(\theta)}{-n-\lambda+1+\iunit\tau_{a,b}(\theta)}{e^{-2\iunit\theta}} = \sum_{\ell=0}^{n}\frac{\Pochhammersym{\lambda+\iunit\tau_{a,b}(\theta)}{\ell}}{\ell!}\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n-\ell}}{(n-\ell)!}e^{\iunit(n-2\ell)\theta}
0 < θ , θ < π formulae-sequence 0 𝜃 𝜃 𝜋 {\displaystyle{\displaystyle 0<\theta,\theta<\pi}}
(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n))/(factorial(n))*exp(I*n*theta)* hypergeom([- n , lambda + I*((a*cos(theta)+ b)/(sin(theta)))], [- n - lambda + 1 + I*((a*cos(theta)+ b)/(sin(theta)))], exp(- 2*I*theta)) = sum((pochhammer(lambda + I*((a*cos(theta)+ b)/(sin(theta))), ell))/(factorial(ell))*(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n - ell))/(factorial(n - ell))*exp(I*(n - 2*ell)*theta), ell = 0..n)
Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n],(n)!]*Exp[I*n*\[Theta]]* HypergeometricPFQ[{- n , \[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, {- n - \[Lambda]+ 1 + I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, Exp[- 2*I*\[Theta]]] == Sum[Divide[Pochhammer[\[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), \[ScriptL]],(\[ScriptL])!]*Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n - \[ScriptL]],(n - \[ScriptL])!]*Exp[I*(n - 2*\[ScriptL])*\[Theta]], {\[ScriptL], 0, n}, GenerateConditions->None]
Error Successful - Successful [Tested: 300]
1.2.E1 n ! ( n - k ) ! k ! = ( n n - k ) 𝑛 𝑛 𝑘 𝑘 binomial 𝑛 𝑛 𝑘 {\displaystyle{\displaystyle\frac{n!}{(n-k)!k!}=\genfrac{(}{)}{0.0pt}{}{n}{n-k% }}}
\frac{n!}{(n-k)!k!} = \binom{n}{n-k}

(factorial(n))/(factorial(n - k)*factorial(k)) = binomial(n,n - k)
Divide[(n)!,(n - k)!*(k)!] == Binomial[n,n - k]
Successful Successful - Successful [Tested: 9]
1.2.E6 ( - 1 ) k ( - z ) k k ! = ( - 1 ) k ( k - z - 1 k ) superscript 1 𝑘 Pochhammer 𝑧 𝑘 𝑘 superscript 1 𝑘 binomial 𝑘 𝑧 1 𝑘 {\displaystyle{\displaystyle\frac{(-1)^{k}{\left(-z\right)_{k}}}{k!}=(-1)^{k}% \genfrac{(}{)}{0.0pt}{}{k-z-1}{k}}}
\frac{(-1)^{k}\Pochhammersym{-z}{k}}{k!} = (-1)^{k}\binom{k-z-1}{k}

((- 1)^(k)* pochhammer(- z, k))/(factorial(k)) = (- 1)^(k)*binomial(k - z - 1,k)
Divide[(- 1)^(k)* Pochhammer[- z, k],(k)!] == (- 1)^(k)*Binomial[k - z - 1,k]
Successful Successful - Successful [Tested: 21]
1.2.E7 ( z + 1 k ) = ( z k ) + ( z k - 1 ) binomial 𝑧 1 𝑘 binomial 𝑧 𝑘 binomial 𝑧 𝑘 1 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{z+1}{k}=\genfrac{(}{)}{0.0% pt}{}{z}{k}+\genfrac{(}{)}{0.0pt}{}{z}{k-1}}}
\binom{z+1}{k} = \binom{z}{k}+\binom{z}{k-1}

binomial(z + 1,k) = binomial(z,k)+binomial(z,k - 1)
Binomial[z + 1,k] == Binomial[z,k]+Binomial[z,k - 1]
Successful Successful - Successful [Tested: 21]
1.2.E8 k = 0 m ( z + k k ) = ( z + m + 1 m ) subscript superscript 𝑚 𝑘 0 binomial 𝑧 𝑘 𝑘 binomial 𝑧 𝑚 1 𝑚 {\displaystyle{\displaystyle\sum^{m}_{k=0}\genfrac{(}{)}{0.0pt}{}{z+k}{k}=% \genfrac{(}{)}{0.0pt}{}{z+m+1}{m}}}
\sum^{m}_{k=0}\binom{z+k}{k} = \binom{z+m+1}{m}

sum(binomial(z + k,k), k = 0..m) = binomial(z + m + 1,m)
Sum[Binomial[z + k,k], {k, 0, m}, GenerateConditions->None] == Binomial[z + m + 1,m]
Successful Successful - Successful [Tested: 21]
1.2.E10 n a + 1 2 n ( n - 1 ) d = 1 2 n ( a + ) 𝑛 𝑎 1 2 𝑛 𝑛 1 𝑑 1 2 𝑛 𝑎 {\displaystyle{\displaystyle na+\tfrac{1}{2}n(n-1)d=\tfrac{1}{2}n(a+\ell)}}
na+\tfrac{1}{2}n(n-1)d = \tfrac{1}{2}n(a+\ell)

n*a +(1)/(2)*n*(n - 1)*d = (1)/(2)*n*(a + ell)
n*a +Divide[1,2]*n*(n - 1)*d == Divide[1,2]*n*(a + \[ScriptL])
Skipped - no semantic math Skipped - no semantic math - -
1.2.E22 M ( r ) = 0 𝑀 𝑟 0 {\displaystyle{\displaystyle M(r)=0}}
M(r) = 0

((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r)) = 0
((Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r)) == 0
Skipped - no semantic math Skipped - no semantic math - -
1.2#Ex1 M ( 1 ) = A 𝑀 1 𝐴 {\displaystyle{\displaystyle M(1)=A}}
M(1) = A

M(1) = ((a[1]+ a[2]+ .. + a[n])/(n))
M[1] == (Divide[Subscript[a, 1]+ Subscript[a, 2]+ \[Ellipsis]+ Subscript[a, n],n])
Skipped - no semantic math Skipped - no semantic math - -
1.2#Ex2 M ( - 1 ) = H 𝑀 1 𝐻 {\displaystyle{\displaystyle M(-1)=H}}
M(-1) = H

M(- 1) = H
M[- 1] == H
Skipped - no semantic math Skipped - no semantic math - -
1.2.E26 lim r 0 M ( r ) = G subscript 𝑟 0 𝑀 𝑟 𝐺 {\displaystyle{\displaystyle\lim_{r\to 0}M(r)=G}}
\lim_{r\to 0}M(r) = G

limit((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r), r = 0) = ((a[1]*a[2] .. a[n])^(1/n))
Limit[(Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r), r -> 0, GenerateConditions->None] == ((Subscript[a, 1]*Subscript[a, 2] \[Ellipsis]Subscript[a, n])^(1/n))
Skipped - no semantic math Skipped - no semantic math - -